AKTIVITAS LIPASE DAN METABOLISME LIPID SELAMA MASA PERKECAMBAHAN WIJEN (Sesamum indicum. L) - Tri Agus Siswoyo; Norry Eka Palupi (JURNAL AGROTEKNOLOGI, 2007)
Experiments were conducted to determine the relationship between lipase activity and the metabolism of lipids during germination of sesame (Sesamum indicum. L) seed. During the course of germination, concentration of the non-polar lipid fractions and lipase activity increased. The glycolipids and phospholipid fractions were relative stable during early germination, but there were marked changes phospholipid fractions after 5 days germination. In a comparison among lipid fractions Non-polar lipids (NL), Glycolipids (GL), and Phospholipids (PL), there were no significant regressions between the quantitative changes in lipid fractions and lipase activities. It was concluded that the degradation in NL and increase in PL and GL observed during sesame germination were not controlled by the level of lipase activity. Rather, it was suggested that sesame may have another lipase present in the cells where the oil bodies are located that hydrolyzes lipids from the oil bodies during germination. Keywords: lipase, glycolipids, phospholipid, lipase, sesame seed